A multi-layered model of human skin elucidates mechanisms of wrinkling in the forehead. (May 2020) - Zhao, Y.; Feng, B.; Lee, J.; Lu, N.; Pierce, D.M.
Abstract: Skin wrinkling, especially in the facial area, is a prominent sign of aging and is a growing area of research aimed at developing cosmetics and dermatological treatments. To better understand and treat undesirable skin wrinkles, it is vitally important to elucidate the underlying mechanisms of skin wrinkling, a largely mechanical process. Human skin, a multi-layer composite, has six mechanically distinct layers: from the outermost inward they are the stratum corneum, viable epidermis, dermal-epidermal-junction, papillary dermis, reticular dermis, and hypodermis. To better address the through-thickness hierarchy, and the development of wrinkling within this complicated hierarchy, we established a six-layered model of human skin realized with finite element modeling, by leveraging available morphological and biomechanical data on human skin of the forehead. Exercising our new model we aimed to quantify the effects of three potential mechanisms of wrinkle formation: (1) skin compression due to muscle contraction (dynamic wrinkles); (2) age-related volumetric tissue loss (static wrinkles); and (3) the combined effects of both mechanisms. Since hydration of the stratum corneum significantly affects its stiffness we also aimed to quantify the influence its hydration with these three potential mechanisms of wrinkle formation. Our six-layered skin model, combined with the proposed wrinkling mechanisms, successfully predicts the formation of dynamic and static wrinkles in the forehead consistent with the experimental literature. We observed three wrinkling modes in the forehead where the deepest wrinkles could reach to the reticular dermis. With further refinement our new six-layered model of human skin can be applied to study other region-specific wrinkle types such as the "crow's feet" and the nasolabial folds. Graphical abstract: (a) A schematic of our six-layered, 3-D skin model; (b) Predicted wrinkling under age-related volumetric tissue loss visualized as through-thickness Green-Lagrange strains with water content (WC) = 36%; (c) Maximum wrinkle depth as a function of age-related volumetric tissue loss shown for three values of WC. Image 1 Highlights: Propose the first six-layered, 3-D skin model to simulate dynamic and static wrinkles. Apply compression up to 25% to model muscle contraction (dynamic wrinkles). Apply age-related volumetric loss within the reticular dermis to model static wrinkles. Simulation results agree well with histological images from forehead wrinkles. Wrinkling mode tracks the development of wrinkles from surface to inner layers.